ZASTOSOWANIE FUNKCJI COBBA-DOUGLASA DO ANALIZY PROCESÓW PRODUKCYJNYCH W POLSKICH PRZEDSIĘBIORSTWACH - Kalinowski, Sławomir (Wydział Prawa i Administracji UAM, 2002)
The article is an attempt at implementing the classic tool of Cobb-Douglas function for the analysis of the influence of two basic production factors on the production size in the selected Polish industries. The statistical verification of the function adaptation has been preceded in the article by verifying the adaptation of the linear function. The major advance on the classic approach is that the explanatory variables have been redefined. The calculation has been based upon the quarterly financial results of companies between 1994 and 1999 from the following industries: shoes, paper and cardboard, pumps and compressors, general building industry, and civil engineering. The source of the data was the „Industry Analysis” drawn up by the Polish Bank of Export Development. The goal of the research was to verify the cognitive value and redefine the variables functioning within the production analysis function as well as to verify the usefulness of the Cobb-Douglas function for analysing the relation between the size of the outlays of production factors and the production size in the selected industries.
IMPLEMENTATION OF COBB-DOUGLAS FUNCTION FOR PRODUCTION PROCESS ANALYSES IN POLISH COMPANIES